Sexual Assault Perpetration and Re-perpetration: From Adolescence to Young Adulthood - Smith, Paige Hall (2004)
Three incoming freshmen classes of men provided data in a 5-year longitudinal study of the relationship between childhood victimization experiences and sexually coercive behaviors during adolescence and 4 years of college. A key finding of this study was that men who were physically punished, sexually abused, or who witnessed domestic violence in childhood were at greater risk for sexual perpetration in high school. Furthermore, men who perpetrated in high school were at greater risk for sexual perpetration in college; and after controlling for perpetration in high school, those who were abused or witnessed violence in childhood were not at greater risk for college perpetration. The findings have a number of implications for research and practice: We need to identify high-risk populations and direct more targeted interventions toward them. These groups include those who witness or experience abuse as a child and young men who perpetrate violence in adolescence, regardless of childhood abuse experiences